The Effect of Financial Literacy and Financial Technology on Financial Performance with Education as a Moderating Variable (Study on MSMEs in the Culinary Sector in Malang City) - Agustina Tri Wulandari; Fitriyah Fitriyah (Cita konsultindo, 2024)
This study aims to determine the effect of financial literacy and financial technology on financial performance with education as a moderating variable. Primary data was used quantitatively as part of the research methodology. Primary data is obtained by distributing questionnaires which aim to collect research data. Sampling using the Slovin formula and the Multistage Cluster Sampling method, 100 MSMEs were obtained. The research findings show that financial technology has a positive and significant impact on financial performance, financial literacy has no real influence on financial performance, and education is unable to moderate the relationship between financial literacy and financial technology on the financial performance of MSMEs.